Multi-stage bioengineering of a layered oesophagus with in vitro expanded muscle and epithelial adult progenitors. Issue 1 (December 2018) - Urbani, Luca; Camilli, Carlotta; Phylactopoulos, Demetra-Ellie; Crowley, Claire; Natarajan, Dipa; Scottoni, Federico; Maghsoudlou, Panayiotis; McCann, Conor; Pellegata, Alessandro; Urciuolo, Anna; Deguchi, Koichi; Khalaf, Sahira; et al.
Abstract A tissue engineered oesophagus could overcome limitations associated with oesophageal substitution. Combining decellularized scaffolds with patient-derived cells shows promise for regeneration of tissue defects. In this proof-of-principle study, a two-stage approach for generation of a bio-artificial oesophageal graft addresses some major challenges in organ engineering, namely: (i) development of multi-strata tubular structures, (ii) appropriate re-population/maturation of constructs before transplantation, (iii) cryopreservation of bio-engineered organs and (iv) in vivo pre-vascularization. The graft comprises decellularized rat oesophagus homogeneously re-populated with mesoangioblasts and fibroblasts for the muscle layer. The oesophageal muscle reaches organised maturation after dynamic culture in a bioreactor and functional integration with neural crest stem cells. Grafts are pre-vascularised in vivo in the omentum prior to mucosa reconstitution with expanded epithelial progenitors. Overall, our optimised two-stage approach produces a fully re-populated, structurally organized and pre-vascularized oesophageal substitute, which could become an alternative to current oesophageal substitutes. Combining decellularised scaffolds with patient-derived cells holds promise for bioengineering of functional tissues. Here the authors develop a two-stage approach to engineer an oesophageal graft that retains the structural organisation of native oesophagus.